(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Myanmar has one of the highest maternal mortality rates in the Southeast Asian region, with most maternal deaths occuring at the time of delivery. The aim of this research was to identify the relationship between socio-demographic characteristics of Myanmar women and utilisation of antenatal care services. Methods: This is a descriptive cross-sectional study utilising the Myanmar Demographic and Health Survey Data 2015-16. A total of 13,454 women agedbetween 15-49 years were surveyed. This study sampled married women only (n=7870). Results: The mean age of the respondents was 35 years and the majority of respondents (50.7%) belonged to the 35-49 age group. Approximately 46.3% of respondents reported more than four antenatal care service (ANC) visits and almost 54% respondents attended ANC during their second and third trimesters. This study found that women with no education, poorer socioeconomic status, less access to mass media, living in rural areas and with more children were not utilising ANC services adequately. Conclusion: Strategies should be introduced to encourage pregnant women to attend a minimum of four antenatal check-ups and there should be adequate monitoring in place of the timing of ANC visits during pregnancy.